Achieving Baby-Friendly Designation at a Large Metropolitan Center - Bruney, Talitha; Campbell, Deborah; Iyare, Abieyuwa (American Journal of Perinatology, 2020)
Objective This study aimed to describe the journey of obtaining Baby-Friendly designation as a large metropolitan center in an urban city and review the initial patient-related outcomes.Study Design Our medical center participated in the New York City Department of Health and Mental Hygiene Breastfeeding Hospital Collaborative from 2012 to 2017. Monthly meetings were held to monitor data, and audits conducted among prenatal sites and maternity units. This hospital collaborative was established to help facilities through the designation process.Results Breastfeeding education in the prenatal setting was provided consistently at all outpatient sites. By 2017, 89.8% of patients had received appropriate education and support during their prenatal visits. There was a shift in feeding pattern from mostly formula feeding with some breastfeeding to primarily breastfeeding with fewer formula feeds. Baby-Friendly designation was achieved in June 2017 after a formal Baby-Friendly USA assessment.Conclusion Since embarking on this journey, there has been a consistent increase in antenatal patient education and a paradigm shift from some breastfeeding to mostly breastfeeding among the mother–baby dyads which combination feed. Our hospital center has continued to successfully maintain the workflow changes implemented during the Baby-Friendly process.
Keywords: breastfeeding; Baby-Friendly; exclusive breastfeeding; infant feeding; prenatal education